Role of Charakokta Medhya Rasayana in the Management of Psychosomatic Disorders - Singh, Archana; Dwivedi, Ashutosh; Khuje, Sanjeev M; Dwivedi, Shriram (International Research Journal of Ayurveda & Yoga, 2023)
In Ayurveda, composition of Sharira (Physical body), Indriya (developed sensory apparatus), Sattva (mind) and Atma (the conscious element) is defined as Ayu, and Sattva, Atma and Sharira are stated as the three pillars of the world. This shows the strong inter relationship between the psyche and the body. So the state of health or disease mainly depends on these two, the mental status of a person affects his physical response to a particular condition as well as to handle stress. This affects the potential appearance and severity of psychosomatic disorders. The incidence of psychosomatic diseases has shown a tremendous increase throughout the world in past few years, and this is all because of faulty life style and stress full environment. Ayurveda is blessed with Rasayana to prevent these problems as it works not only on healthy peoples but on diseased too. In one hand it promotes the formation of better quality body tissues by this promoting the physical health; on the other hand it enhances the mental status of the individual and by this promoting the psychic health. Ayurveda describes a special class of promotive agents called Medhya Rasayana claimed to promote mental health. So rasayana therapy can be taken as a new approach for prevention and treatment of psychosomatic disorders.